Multi-Channel Seismic Shot Data from the Iberia Abyssal Plain and Galicia Bank acquired during the R/V Maurice Ewing expedition EW9705 (1997) (IEDA: Marine-Geo Digital Library, 2004)
This data set was acquired with the LDEO Multi-Channel Seismic system during R/V Maurice Ewing expedition EW9705 conducted in 1997 (Chief Scientist: Dr. Dale Sawyer). These data files are of SEGY format and include Multi-Channel Seismic Reflection shot data that have not been processed. Data were acquired as part of the project: The S Reflector and Rifting Processes: Iberia Abyssal Plain/Galicia Bank, and funding was provided by NSF grant: OCE95-21517.